Seroprevalence of hepatitis B and C virus infections and risk factors in Turkey: a fieldwork TURHEP study. (November 2015) - Tozun, N.; Ozdogan, O.; Cakaloglu, Y.; Idilman, R.; Karasu, Z.; Akarca, U.; Kaymakoglu, S.; Ergonul, O.
Abstract: The present study was designed to determine the seroprevalence of hepatitis B and C virus (HBV, HCV) infections and risk factors in the Turkish general population. Participants were enrolled from urban and rural areas of the predetermined 23 EUROSTAT NUTS 2 region. A two-stage stratified sampling method was used to select participants from these regions ( n = 5460; 50.9% females; mean (SD) age: 40.8 (14.7) years). Sociodemographics, clinical characteristics and risk factors were recorded at home visits. The seropositivity rates for hepatitis B surface antigen (HBsAg), anti-HCV, anti-HBs and anti-HBc total were 4.0%, 1.0%, 31.9% and 30.6%, respectively. Among HBsAg-positive cases, 94.5% were anti-HBe-positive, 70.2% were HBV-DNA-positive and 2.8% were anti-HDV total positive; 99.1% of HBV infections were of genotype D. Close contact with a hepatitis patient (OR 3.24; 95% CI 2.25–4.66; p < 0.001), living in the southeastern region (OR 2.74; 95% CI 1.7–4.45; p < 0.001), male gender (OR 1.77; 95% CI 1.28–2.46; p < 0.001), being married (OR 1.62; 95% CI 1.02–2.57; p 0.038), educational level less than high school (OR 1.53; 95% CI 1.04–2.26; p 0.03), orodental interventions (OR 1.54; 95% CI 1.01–2.35; p 0.047) and a history of non-disposable syringe use (OR 1.4; 95% CI 1.01–1.96; p 0.045) were significant determinants of HBsAg positivity. Age ≥50 years (OR 2; 95% CI 1.09–4.3; p 0.026) was the only significant predictor of anti-HCV positivity. In conclusion, our findings revealed an HBsAg positivity in 4% and anti-HCV positivity in 1% of the adult population and at least one-third of the population has been exposed to HBV infection in Turkey.